TINJAUAN YURIDIS TINDAK PIDANA PENGEDARAN SEDIAAN FARMASI TANPA IZIN EDAR MENURUT UNDANG-UNDANG NOMOR 36 TENTANG KESEHATAN - Menteng Menteng (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTION      Sediaan Pharmacy represent a art in the world of effort, where someone having ability in managing materialss either from flora, chemical Iihat vitamin, materials of sintetis becoming a high valuable erudite masterpiece, which can assist mankind which in a state of pain, so that deflect to give recovering [at] one who [is] ill the than [his/its] suffered disease.      But pharmacy sediaan can also cause patal to its consumer, what if/when at the (time) of producing and circularizing or marketing pharmacy sediaan to society [there] no observation of Minister for Public Health and Body Supervisor Medicinize and Food ( BPOM). To prevent effect of which is generated hence pharmacy sediaan have to permit mendapt of intansi in charge, that appliance or drug health of diffraction circularized to society and do not danger menumbulkan to consumer if used as according to order which have in determining by kefermasian.     Pursuant to regulation of government of Number 72 Year 1998 section 1 letter ( a) about Security of Sediaan Pharmacy and Appliance Health, and number code 36 year 2009 section 1 number ( 4), sounding: Sediaan Pharmacy is drug, drug materials, traditional drug and cosmetic.      Pursuant To Evaluation Doing An Injustice Circulating Of Sediaan Pharmacy Without Permit Circulate, according to section 39 sentence ( 1) PP number 72 year 1998 sounding: ( 1) If result of examination return pharmacy sediaan and appliance health of pharmacy sediaan menunjukan and pertinent health appliance do not fulfill conditions of quality, security, and benefit or can generate health danger to human being, pharmacy sediaan and health appliance which is is pertinent to be abstracted by permit circulate him  From at that society have to be brooding when using pharmacy sediaan and health appliance circulating, and if there are generating. Keyword: Sediaan Pharmacy without permit circulate according to UU No.36 about health.